Comportamiento de la fuerza de atracción y repulsión de dos tipos de imanes para movimiento ortodóntico (2022)
The central objective of the document is to determine the force of tension and repulsion generated by two types of magnetic alloys in Neodymium and Samarium Cobalt in order to incorporate them into the movement in orthodontics. To carry out this, two groups corresponding to the two alloys were classified and each one with three samples corresponding to the thickness of the magnets 4mm, 5mm and 6mm in order to determine the effective force that these generated at a distance of 0 to 6 millimeters. , it is possible to demonstrate through the tests carried out in the universal testing machine an increase in the force generated in the compression test 89.2 g/f for both alloys; For the tension test, a loss of force of 19.2 g/f was observed with increasing distance from the devices to the magnets, with the neodymium magnet presenting the best properties.